2008
DOI: 10.1111/j.1365-2486.2008.01680.x
|View full text |Cite
|
Sign up to set email alerts
|

Impact of past and present land‐management on the C‐balance of a grassland in the Swiss Alps

Abstract: Grasslands cover about 40% of the ice-free global terrestrial surface, but their quantitative importance in global carbon exchange with the atmosphere is still highly uncertain, and thus their potential for carbon sequestration remains speculative. Here, we report on CO 2 exchange of an extensively used mountain hay meadow and pasture in the Swiss pre-Alps on high-organic soils (7-45% C by mass) over a 3-year period (18 May 2002-20 September 2005, including the European summer 2003 heat-wave period. During all… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
68
2

Year Published

2010
2010
2018
2018

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 58 publications
(76 citation statements)
references
References 38 publications
6
68
2
Order By: Relevance
“…They also indicate that soils of our study sites were characteristic of European fens and resembled typical properties of managed organic soils (Berglund, 1995;Kechavarzi et al, 2010;Eickenscheidt et al, 2015;Krueger et al, 2015;Wüst-Galley et al, 2016;Brouns et al, 2016). Several studies assume that deeper layer peat of managed organic soils is less decomposed (Ewing and Vepraskas, 2006;Rogiers et al, 2008;Leifeld et al, 2011a, b;Krueger et al, 2015;Wüst-Galley et al, 2016). We therefore interpret the different SOM characteristics found in the topsoils of our samples as indicators of advanced decomposition triggered by drainage.…”
Section: Som Characteristicsmentioning
confidence: 85%
See 2 more Smart Citations
“…They also indicate that soils of our study sites were characteristic of European fens and resembled typical properties of managed organic soils (Berglund, 1995;Kechavarzi et al, 2010;Eickenscheidt et al, 2015;Krueger et al, 2015;Wüst-Galley et al, 2016;Brouns et al, 2016). Several studies assume that deeper layer peat of managed organic soils is less decomposed (Ewing and Vepraskas, 2006;Rogiers et al, 2008;Leifeld et al, 2011a, b;Krueger et al, 2015;Wüst-Galley et al, 2016). We therefore interpret the different SOM characteristics found in the topsoils of our samples as indicators of advanced decomposition triggered by drainage.…”
Section: Som Characteristicsmentioning
confidence: 85%
“…The samples were stored at 4 • C for up to 2 months until analysis. We applied the method of Rogiers et al (2008) to account for soil compaction during sampling for any sample and divided the cores into segments corresponding to 5-10 cm depth increments. This corresponded, depending on the type of soil corer used and length of the increment, to sample volumes of between 31 and 196 cm 3 per segment.…”
Section: Soil Samplingmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, net CO 2 release (F CO 2 , 0) is associated with organic-rich soils and heat stress. Indeed, a net CO 2 release was found with drained organic soils subjected to grazing in Switzerland and in New Zealand (Nieveen et al, 2005;Rogiers et al, 2008), and these sites were found to lose C (i.e. negative NCS; Table 1).…”
Section: Grassland Carbon Sequestrationmentioning
confidence: 99%
“…Carbon flux studies show that NCS is affected by a number of site-specific factors, including grassland type (newly established v. permanent, Byrne et al, 2005), N fertiliser supply , grazing pressure , drainage (Nieveen et al, 2005;Rogiers et al, 2008) and burning (Suyker and Verma, 2001) (Table 1). In addition, annual rainfall, temperature and radiation (Hunt et al, 2004;Ciais et al, 2005;Gilmanov et al, 2007;Soussana et al, 2007) play an important role for the variability in NCS between years and between sites.…”
Section: Grassland Carbon Sequestrationmentioning
confidence: 99%